A phase 1 study to evaluate the safety and pharmacokinetics of PQ912, a glutaminyl cyclase inhibitor, in healthy subjects. Issue 3 (2nd October 2015) - Lues, Inge; Weber, Frank; Meyer, Antje; Bühring, Uli; Hoffmann, Torsten; Kühn‐Wache, Kerstin; Manhart, Susanne; Heiser, Ulrich; Pokorny, Rolf; Chiesa, Joseph; Glund, Konrad
Abstract: Introduction: Pyroglutamate‐amyloid‐β (pE‐Aβ) peptides are major components of Aβ‐oligomers and Aβ‐plaques, which are regarded as key culprits of Alzheimer's disease (AD) pathology. PQ912 is a competitive inhibitor of the enzyme glutaminyl cyclase (QC), essential for the formation of pE‐Aβ peptides. Methods: A randomized, double‐blind, placebo‐controlled, single‐ and multiple‐ascending oral dose study investigated the safety, pharmacokinetics, and pharmacodynamics of PQ912 in healthy nonelderly and elderly subjects. Results: PQ912 was considered safe and well tolerated with dose‐proportional pharmacokinetics up to doses of 200 mg. At higher doses up to 1800 mg, exposure was supraproportional and exposure in elderly subjects was approximately 1.5‐ to 2.1‐fold higher. Exposure in cerebrospinal fluid (CSF) was approximately 20% of the unbound drug in plasma, and both serum and CSF QC activity was inhibited in a dose‐related manner. Discussion: This first‐in‐man study of a compound‐targeting QC inhibition justifies further development of PQ912 for the treatment of AD.